New postgraduate students’ orientation programme - Joseph, Corina (UiTM Sarawak, 2016)
The Centre of Graduate Studies, UiTM Sarawak organised an orientation programme to welcome all new September 2015 intake students on 12th September 2015 at the Riverside Majestic Hotel, Kuching. Approximately 23 new research and coursework students turned up to register. The programme started with a networking lunch followed by the registration at 2.00 pm. Subsequently, the students attended a briefing by respective Research and Coursework Coordinators, Associate Professor Dr Corina Joseph and Ms Siti Huzaimah Sahari. The briefing covered rules and regulations pertaining to programmes and important dates throughout the semester. Officers from the Bursary Department and the library also conducted their briefings for the new students. Lastly, the closing ceremony of the programme was officiated by the Head of Centre of Graduate Studies, UiTM Sarawak, Associate Professor Dr Firdaus Abdullah at 6.00 pm.